1978
DOI: 10.1016/s0022-5347(17)57448-0
|View full text |Cite
|
Sign up to set email alerts
|

Micturition Urodynamic Flow Studies in Children

Abstract: Voiding abnormalities are encountered frequently in pediatric patients. Symptoms of daytime incontinence, frequency and nocturnal enuresis in any combination may indicate underlying neurophysiologic detrusor imbalance. Incomplete evaluation of these symptoms can result in inappropriate medical therapy or even ineffective operations. Within the preceding 7 months 34 children with hard-core voiding abnormalities were evaluated with urodynamic techniques. Several categories of abnormal voiding patterns were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Urodynamically proven bladder instability has frequently bcen emphasimd as the possible cause of enuresis. Daytime urodynamic investigations have shown that bladder instability occurs in 29-90% of the investigated cases [Firlit et al, 1978;Kahn et al, 1984;Mahoney et al, 1977a,b;McGuire and Savastano, 1984;Palmtag et al, 1975); Webster et al,15)84a,b]. This broad spectrum of incidence in bladder instability may be explained by differences in the patient matcrial investigated and in investigational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Urodynamically proven bladder instability has frequently bcen emphasimd as the possible cause of enuresis. Daytime urodynamic investigations have shown that bladder instability occurs in 29-90% of the investigated cases [Firlit et al, 1978;Kahn et al, 1984;Mahoney et al, 1977a,b;McGuire and Savastano, 1984;Palmtag et al, 1975); Webster et al,15)84a,b]. This broad spectrum of incidence in bladder instability may be explained by differences in the patient matcrial investigated and in investigational methods.…”
Section: Introductionmentioning
confidence: 99%
“…evaluation of non-neurogenic neurogenic bladder syndromes can result in inappropriate medical therapy or From 1994 to 1997, 120 children (38 boys and 82 girls, mean age 7.5 years, range 5-9) were retrospeceven ineCective surgery [1]. A standard urodynamic evaluation is not always well tolerated in children, tively evaluated by one urologist (C.P.)…”
Section: Methodsmentioning
confidence: 99%
“…A dyscoordination between the detrusor and the activity of the pelvic floor was thought to be the cause of the condition. This possible mechanism was later evi denced by urodynamic investigations in children with enuresis and recurrent urinary tract infections [3][4][5], The present investigation was undertaken in order to describe the symptomatology and the clinical manifesta tions of the detrusor sphincter dyssynergia in patients without neurological manifestations. …”
mentioning
confidence: 92%